Parasitoid species of the genera Ascogaster and Chelonus (Hymenoptera: Braconidae: Cheloninae) from the Marmara, Western and Middle Black sea Regions of Turkey - Aydogdu, M. (Acta entomologica slovenica (Ljubljana), 2007)
Coleoptera, Diptera, Hymenoptera and Lepidoptera larvae, which occur commonly in orchards, vegetable areas, crop fields and forests, are frequently accompanied by a considerable number of natural enemies. A great importance innature is attributed to the parasitoid insects belonging to the genera of Ascogaster and Chelonus. Even infrequent treatments of insecticides on plantations limit the population of parasitoids and reduce their species richness. Ascogaster and Chelonus species play the greatest role in parasitization of Lepidoptera. Twenty-six species of Coleoptera, Diptera, Hymenoptera and Lepidoptera parasitoids were found in this study. Ascogaster excisa, A. gonocephala, A. grahami, A. varipes, Chelonus (C.) annulipes, C. (C.) annulatus, C. (C.) caradrinae, C. (C.) elongates and C. (C.) processiventris are reported for the first time from Turkey. The relationshipswith hosts, the species and their habitats are given in the table. This study ought to be an important first step to integrated pest management studies which will be accomplished in the future.
Keywords: entomologija; favna; parazitizem; plantaže; Turčija; Turkey